2017
DOI: 10.1200/jgo.2016.006023
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Implementation of Antiemetic Prescription Standards in Indian Oncology Practices and Its Adherence to the American Society of Clinical Oncology Antiemetic Clinical Guideline

Abstract: PurposeAdherence to international antiemetic prophylaxis guidelines like those of ASCO can result in better control of chemotherapy-induced nausea and vomiting; however, the extent of implementation of such guidelines in India is unknown. Therefore, this survey was planned.MethodsThis study was an anonymized cross-sectional survey approved by the ethics committee. Survey items were generated from the clinical questions given in the ASCO guidelines. The survey was disseminated through personal contacts at an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For patients who received a low emetogenic regimen, 68.5% received unnecessary prophylaxis. 14 Another study by Patil et al 15 had similar findings.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…For patients who received a low emetogenic regimen, 68.5% received unnecessary prophylaxis. 14 Another study by Patil et al 15 had similar findings.…”
Section: Introductionmentioning
confidence: 64%
“…According to sample size calculation method for determining a sample proportion, a maximum sample size of 131 is required for a proportion of 40%–60%, a confidence interval width of 12%, and a significance level of 0.05. 14 , 15 Ethical approval for this study was deemed exempt by National Guard Health Affairs Research Committee, Saudi Arabia. Patient consent is not applicable since only existing medical records were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence-based practice guidelines recommend its use both upfront and in patients with uncontrolled nausea and vomiting [ 3 , [23] , [24] , [25] , [26] ]. However, there has been limited incorporation of olanzapine into broader clinical practice [ 27 , 28 ]. This likely reflects concerns around its sedative and extra pyramidal effects [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Indian oncologists largely depend upon the National Comprehensive Cancer Network (NCCN) recommendations, the American Society of Clinical Oncology (ASCO) clinical updates and European society for medical oncology/multinational Association of Supportive Care in Cancer (ESMO/MASCC) recommendations. However, it is pertinent to state that these global guidelines are tailored according to the functioning of the healthcare setups in developed nations and do not account for factors unique to the healthcare systems of developing countries (19). Healthcare dynamics in a developing economy as ours are different from those of the developed nations.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare dynamics in a developing economy as ours are different from those of the developed nations. Healthcare accessibility, coupled with issues such as variable management practices and lack of sensitization for guidelines, has made the development of region-specific CINV-management guidelines the need of the hour (19). Findings from previously conducted multination Pan Australasian ChemoTherapy InduCed Emesis burden of illness (PrACTICE) study reported vast variation in the complete response (CR) rate (∼50-87%) among patients from different participating countries (20).…”
Section: Introductionmentioning
confidence: 99%